Personal Impressions Updated Edition - Berlin, Isaiah 1909-1997 (Princeton University Press, 2014)
In this collection of remarkable biographical portraits, the great essayist and intellectual historian Isaiah Berlin brings to life a wide range of prominent twentieth-century thinkers, politicians, and writers. These include Winston Churchill, Franklin D. Roosevelt, Chaim Weizmann, Albert Einstein, Virginia Woolf, Aldous Huxley, Boris Pasternak, and Anna Akhmatova. With the exception of Roosevelt, Berlin met them all, and he knew many of them well. Other figures recalled here include the Zionist Yitzhak Sadeh, the U.S. Supreme Court judge Felix Frankfurter, the classicist and wit Maurice Bowra, the philosopher J. L. Austin, and the literary critic Edmund Wilson. For this edition, ten new pieces have been added, including portraits of David Ben-Gurion, Maynard and Lydia Keynes, and Stephen Spender, as well as Berlin's autobiographical reflections on Jewish Oxford and his Oxford undergraduate years. Rich and enlightening, Personal Impressions is a vibrant demonstration of Berlin's belief that ideas truly live only through people